Saponin Biji Klabet pada Organ Reproduksi Tikus Jantan Sprague Dawley® - Sri Nita; Ummi Hiras Habisukan; Nyayu Fauziah Zen (Jurnal Penelitian Sains, 2016)
Fenugreek seed saponin is one alternative of antifertilitas medicinal plants. Research purposes is to determine the effect of the fenugreek seeds saponin againts the reproductive organ, that is weight and histological structure of the testis and epididymis Sprague Dawley® rat. Research design using randomized design complete. The control group was given distilled water, the treatment group were given fenugreek seed saponin with doses of 40, 80, & 120 mg/kg bw. Treatment is administered orally 1x/day for 24 days. Award saponin start dose of 40 mg/kg bw can reduce the weight of the testes and reduce the size of the diameter of seminiferous tubules. Thick germ cells begin to be affected at higher doses, 120 mg/kg bw. Epididymis weight is reduced significantly compared to the control start at dose 80 mg/kg bw and giving a higher dose, 120 mg/kg bw significantly further reduces the weight of the epididymis. Saponin administration starting dose of 80 mg/kg bw already significantly reduced the thickness of the epithelium of the epididymis. Giving a higher dose of 120 mg/kg bw increasingly signifcant cause epididymal epithelium thickness thinner. It can be concluded that the administration of saponin fenugreek seeds caused a reduction in weight and histological changes in the testis and epididymis structure of rat Spraque Dawley®